The Implementation Using Video for Learning of Sepak Sila Technique - Silvi Aryanti; Wahyu Indra Bayu; Ahmad Richard Victorian; Samsul Azhar (Universitas Negeri Medan, 2021)
This study aims to determine the implementation of the use of the learning model using video in the learning of the precepts of the Sepak Takraw course. This research is research and development. The subjects of this study were students of Physical Education, Faculty of Teacher Training and Education, Universitas Sriwijaya. Small-scale product trials were conducted on 20 students, and large-scale trials were carried out on 30 students. The results of small-scale trial research obtained a percentage of 64.25 with a fairly good category, and the results of large-scale trials obtained a percentage of 77.51 with a good category. The results obtained indicate that the learning model using video is feasible to be used in learning the basic techniques of football in the takraw course.